ORIGIN OF PARTICLES ACCORDING TO PHYSICS AND METAPHYSICS - Shrivas, Chandrashekhar; Sharma, Kadambari; Khuntian, Sheela (International Journal of Research -GRANTHAALAYAH, 2024)
The origin of particles has been the subject of intense exploration in both physics and metaphysical philosophy. In physics, particles are understood as the basic components of matter, whose origin is linked to the Big Bang and the subsequent evolution of the universe. Quantum mechanics further complicates this understanding, suggesting that particles may emerge from energy and undergo transformation under specific conditions. Metaphysical philosophy, on the other hand, delves deeper into ontological questions about the nature and essence of particles, exploring their role in larger cosmic and existential frameworks. This paper examines the origin of particles from these two different but interconnected perspectives—physics and metaphysical philosophy, shedding light on empirical theories based on scientific observation and philosophical investigations into the objective and fundamental nature of particles. By comparing and contrasting both perspectives, this paper attempts to provide a more holistic understanding of the origin and nature of particles, linking the empirical with the speculative, and providing insights into how both disciplines contribute to our conception of the building blocks of the universe.